Citizenship and Social Class: A Study of the Thoughts of Thomas Humprey Marshall and Tom Bottomore - Ranita Eka Desti Rahmawati; Samsuri Samsuri; Maria Antoneta Karbeka; Ariani Songli (Sean Institute, 2026)
This article examines T.H. Marshall's thoughts on citizenship and social class as reflected in his book Citizenship and Social Class. T.H. Marshall divides citizenship into three main elements: civil rights, political rights, and social rights. Social rights, which include education, health, and social welfare, are the focus in reducing social inequality in society. Although civil and political rights have developed, T.H. Marshall emphasises that social rights still face major challenges in achieving equality. This study also integrates Tom Bottomore's view, which highlights the limitations of the state in providing social rights amid a capitalist system that emphasises market efficiency. This research is relevant to the conditions in Indonesia, which still faces inequalities in access to education, health, and social protection, despite affirmative policies such as the Family Hope Programme (PKH) and National Health Insurance (JKN). By analysing the thoughts of T.H. Marshall and Tom Bottomore, this study provides a perspective in understanding the relationship between citizenship, social class, and social inequality, as well as the importance of more inclusive policies in creating equal citizenship in Indonesia.